2014
DOI: 10.1002/jnr.23536
|View full text |Cite
|
Sign up to set email alerts
|

Neural systemic impairment from whole‐body vibration

Abstract: Insidious brain microinjury from motor vehicle-induced whole-body vibration (WBV) has not yet been investigated. For a long time we have believed that WBV would cause cumulative brain microinjury and impair cerebral function, which suggests an important risk factor for motor vehicle accidents and secondary cerebral vascular diseases. Fifty-six Sprague-Dawley rats were divided into seven groups (n = 8): 1) 2-week normal control group, 2) 2-week sham control group (restrained in the tube without vibration), 3) 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 22 publications
1
18
0
Order By: Relevance
“…People believe tired drivers are deadly drivers. However, our recent preliminary study results 1–3 on simulated motor vehicle-induced whole-body vibration (MV-WBV) challenge the traditional thinking; our studies suggest that “driver’s fatigue” is actually brain dysfunction and brain impairment resulting from MV-WBV. Here we hypothesize that prolonged MV-WBV induces brain injuries that compromise a driver’s judgment and reactive capabilities and may be one cause of MVAs.…”
Section: Introductionmentioning
confidence: 71%
See 3 more Smart Citations
“…People believe tired drivers are deadly drivers. However, our recent preliminary study results 1–3 on simulated motor vehicle-induced whole-body vibration (MV-WBV) challenge the traditional thinking; our studies suggest that “driver’s fatigue” is actually brain dysfunction and brain impairment resulting from MV-WBV. Here we hypothesize that prolonged MV-WBV induces brain injuries that compromise a driver’s judgment and reactive capabilities and may be one cause of MVAs.…”
Section: Introductionmentioning
confidence: 71%
“…Seventy-two Sprague-Dawley male rats (weight 250–300 g) were divided into 9 groups (N = 8) 1 : the 2-week normal control group had no treatment 2 ; the 2-week sham control group was restrained in the tube without vibration 3 ; the 2-week vibration group was exposed to WBV at 30 Hz and .5 g acceleration for 4 hours/day, 5 days/week for 2 weeks 4 ; the 4-week sham control group was restrained in the tube without vibration 5 ; the 4-week vibration group was vibrated for 4 weeks 6 ; the 4-week vibration group was treated with 4F-peptide (Ac-DWFKAFYDKVAEKFKEAF-NH2) preconditioning 7 ; the 8-week sham control group was restrained in the tube without vibration 8 ; the 8-week vibration group was vibrated for 8 weeks 9 ; and the 8-week vibration group was treated with 4F-peptide preconditioning. At the end point, all the rats were evaluated by behavioral, physiological, histopathological, and molecular studies of the brain.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Short time exposure to WBV has shown to have physiological effects which includes hyperventilation, chest pain and increased muscle tension 4. Yan et al 19 hypothesised that acute WBV exposure caused insidious brain injury by bringing about cerebrovascular spasm, constriction and increased amount of free radicals leading to neuronal impairment which further causes fatigue. It was observed that with 1 hour exposure, the rms value of HAV was below the EAV and ELV.…”
Section: Discussionmentioning
confidence: 99%